2002
DOI: 10.1038/sj.onc.1205962
|View full text |Cite
|
Sign up to set email alerts
|

Tuberin, the tuberous sclerosis complex 2 tumor suppressor gene product, regulates Rho activation, cell adhesion and migration

Abstract: Tuberous sclerosis complex (TSC) is a tumor suppressor gene syndrome characterized by seizures, mental retardation, autism, and tumors of the brain, kidney, heart, retina, and skin. TSC is caused by mutations in either TSC1 or TSC2, both of which are tumor suppressor genes. Hamartin, the protein product of TSC1, was found to interact with the ezrin-radixin-moesin family of cytoskeletal proteins and to activate the small GTPase Rho. To determine whether tuberin, the TSC2 product, can also activate Rho, we stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
102
4
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(112 citation statements)
references
References 43 publications
5
102
4
1
Order By: Relevance
“…In many systems, Akt1 has been shown to phosphorylate TSC2, triggering 14-3-3-dependent proteolytic degradation (16,19). Moreover, elevated TSC2 and TSC1 have been shown to increase Rho activity in epithelial Madin-Darby canine kidney cells (15) and in fibroblasts (47), respectively. Accordingly, we hypothesized that Akt1-mediated inhibition of Rho activity was the consequence of phosphorylation and downmodulation of TSC2.…”
Section: Active Akt1 Controls Migration and Invasion By Modulating Lementioning
confidence: 99%
See 2 more Smart Citations
“…In many systems, Akt1 has been shown to phosphorylate TSC2, triggering 14-3-3-dependent proteolytic degradation (16,19). Moreover, elevated TSC2 and TSC1 have been shown to increase Rho activity in epithelial Madin-Darby canine kidney cells (15) and in fibroblasts (47), respectively. Accordingly, we hypothesized that Akt1-mediated inhibition of Rho activity was the consequence of phosphorylation and downmodulation of TSC2.…”
Section: Active Akt1 Controls Migration and Invasion By Modulating Lementioning
confidence: 99%
“…Although it has been best characterized as a controller of cell size through its regulation of ribosomal synthesis proteins including ribosomal S6 kinase (17,18), TSC2 has been implicated in a number of related signaling pathways in a variety of cell types (19). Investigations of Madin-Darby canine kidney epithelial cells demonstrated that overexpression of TSC2 results in activation of Rho and increased cellular motility (15), and analysis of TSC2-deficient cells has shown reduced Rho activity (16), although these effects may depend on the cell type investigated (20). Although mutational inactivation of TSC2 contributes to tuberous sclerosis complex, regulation of intact TSC2 occurs principally through the action of the serine͞threonine kinase Akt1͞protein kinase B (21,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both hamartin and tuberin activate members of the Rho GTPase superfamily, which regulate the actin cytoskeleton, cell morphology and migration, and induce focal adhesions (Lamb et al, 2000;Astrinidis et al, 2002;Goncharova et al, 2004). Tuberin-deficient smooth muscle cells exhibit increased migration in vitro, compared to cells with reintroduction of wild-type tuberin, and decreased RhoA-GTP (Astrinidis et al, 2002). Tuberin expression increases the in vitro attachment of cells on plastic, consistent with decreased expression of focal adhesion kinase (FAK) and increase in the fraction of phospho-FAK (Astrinidis et al, 2002).…”
Section: Pulmonary Manifestations Of Tsc -The 'Benign Metastasis' Modelmentioning
confidence: 99%
“…16 We found that cells lacking Tsc2 have lower levels of Rho activity, enhanced chemotactic cell migration, and decreased cell adhesion. 17 Goncharova et al 18,19 found that TSC2 regulates cell migration and impacts the activity of both Rac and Rho. Interestingly, they found that the N-terminus of TSC2 was sufficient to inhibit cell migration and activate Rac1, suggesting that this is independent of the GTPase-activiating protein (GAP) activity of tuberin and independent of Rheb.…”
Section: Loss Of Tsc1 And=or Tsc2 Enhances Cell Migration and Invasionmentioning
confidence: 99%